1 in both cases. There will be a difference only in phase. But you may have stated the problem incorrectly.
2006-12-10 17:22:02
·
answer #1
·
answered by nor^ron 3
·
0⤊
1⤋
Each is a wave with amplitude unity (the coefficient before the sin term). For example, at x and t=0, the amplitude of the first wave is zero and that of the second wave close to -1 (sin(3) = sin(pi) nearly). At given values of x and t, one wave will be so offset from the other, so I would guess this is the maximum value of the resultant wave. Is this a trick?
2006-12-10 17:27:15
·
answer #2
·
answered by cattbarf 7
·
0⤊
1⤋
y1 = sin(4x-3t), y2 = sin
Amplitude of y1 = amplitude of y2 = 1
y1 + y2 = sin(4x - 3t) + sin(4x - 3t + 3)
Let u = 4x - 3t + 3/2
Thus 4x - 3t = u - 3/2 and 4x - 3t + 3 = u + 3/2
So y = y1 + y2 = sin(u - 3/2) + sin (u + 3/2)
= 2 sin [½((u + 3/2) + (u - 3/2))] cos [½((u + 3/2) - (u - 3/2))]
= 2sinucos(3/2)
= [2cos(3/2)]sinu
dy/du = 2cos(3/2) cosu = 0 for stationary points
So u = π/2, 3π/2 (for 0 ≤ u ≤ 2π)
When u = π/2 sin u = 1 and when u = 3π/2 sinu = -1
Whence y1 + y1= sin(u - 3/2) + sin (u + 3/2)
and sin (3π/2 - 3/2) + sin (3π/2 + 3/2) ≤ y1 + y2 ≤ sin (π/2 - 3/2) + sin (π/2 + 3/2)
ie -0.1414744.... ≤ y1 + y2 ≤ 0.1414744....
So its amplitude is 0.1414744.... (= 2 cos (3/2))
2006-12-10 18:02:15
·
answer #3
·
answered by Wal C 6
·
0⤊
0⤋
sin(4x-3t) + sin(4x-3t+3) = 2sin((8x-6t+3)/2)cos(-3/2)
now if we compare with Asin(wt+kx) we have:
A = 2cos(-3/2)=2cos(3/2)
2006-12-10 17:24:35
·
answer #4
·
answered by SaturnReLnArimani 2
·
1⤊
0⤋